The Influence of Process Parameters on Stability Of Water-In-Crude Oil Emulsion Stabilized by Span 80 - Akbari, Sweeta; Nour, A. H.; Fayaz, Fahim (IJESRT, 2015)
There is a wide range of scientific literature related to emulsion stability, most of them dealt with water-in-oil (W/O) or oil-in-water (O/W) type. The present work is aimed to investigate the stability mechanisms of water-in-crude oil emulsion stabilized by a non-ionic emulsifier (Span 80). The blending of (50-50 vol. %) heavy and light crude oil was first characterized in terms of physico-chemical properties. The emulsion was stabilized by (1.5 and 2.5 vol. %) emulsifier at different water: oil ratio of (20-80 vol. %) and (40-60 vol. %). According to the result of microscopy images, the steric stability was obtained in low water volume fraction content (20%), with the smaller droplet sizes and at higher surfactant concentration (2.5%). The emulsions stabilized with Span 80 obtained a visually stable emulsion in both concentrations of emulsifier and volume fractions of dispersed phase (water) in a period of one week,and there was no water separation was observed in this period. To determine the dynamic viscosity rate, the temperature was varied from 30 ºC to 90 ºC and shear rate from (17 to 85)1/sec respectively. Moreover, the emulsion with the higher water volume fraction (40%) and emulsifier concentration of 2.5 % indicated higher dynamic viscosity.However, in all types of the samples, the dynamic viscosity decreased by increasing the shear rate. The results obtained in this study have exposed the capability of the chosen emulsifier as another promising method for stabilizing w/o emulsions. Further works are, nevertheless, required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry